CRISPR-Cas9 assisted gene disruption in the higher fungus Ganoderma species. (May 2017) - Qin, Hao; Xiao, Han; Zou, Gen; Zhou, Zhihua; Zhong, Jian-Jiang
Graphical abstract: Highlights: CRISPR-Cas9 assisted gene disruption was demonstrated for the first time in higher fungi. The ura3 gene of Ganoderma lucidum was disrupted by the codon-optimized Cas9 and in vitro transcribed gRNA. This work may help to provide a widely applicable approach of gene disruption in higher fungi. Abstract: Higher fungi are regarded as promising cell factories for production of bioactive secondary metabolites, but there is a lack of methods of genetic manipulation, such as gene disruption, which hinders the studies on biosynthesis and its regulation of those useful natural products. In this study, the CRISPR-Cas9 assisted gene disruption was established for the first time in higher fungi by taking Ganoderma species as typical examples. With double strand break (DSB) introduced by CRISPR-Cas9, non-homologous end joining (NHEJ) was induced and further assisted the gene disruption. As proof of concept, the ura3 gene of G. lucidum 260125 and G. lingzhi was successfully disrupted by the codon-optimized Cas9 and in vitro transcribed gRNA. This work may help to provide a widely applicable approach of gene disruption in higher fungi.